Physiological Studies of Chlorobiaceae Suggest that Bacillithiol Derivatives Are the Most Widespread Thiols in Bacteria - Jennifer Hiras (American Society for Microbiology, 2018)
ABSTRACT Low-molecular-weight (LMW) thiols mediate redox homeostasis and the detoxification of chemical stressors. Despite their essential functions, the distribution of LMW thiols across cellular life has not yet been defined. LMW thiols are also thought to play a central role in sulfur oxidation pathways in phototrophic bacteria, including the Chlorobiaceae. Here we show that Chlorobaculum tepidum synthesizes a novel LMW thiol with a mass of 412 ± 1 Da corresponding to a molecular formula of C14H24N2O10S, which suggests that the new LMW thiol is closely related to bacillithiol (BSH), the major LMW thiol of low-G+C Gram-positive bacteria. The Cba. tepidum LMW thiol structure was N-methyl-bacillithiol (N-Me-BSH), methylated on the cysteine nitrogen, the fourth instance of this modification in metabolism. Orthologs of bacillithiol biosynthetic genes in the Cba. tepidum genome and the CT1040 gene product, N-Me-BSH synthase, were required for N-Me-BSH synthesis. N-Me-BSH was found in all Chlorobiaceae examined as well as Polaribacter sp. strain MED152, a member of the Bacteroidetes. A comparative genomic analysis indicated that BSH/N-Me-BSH is synthesized not only by members of the Chlorobiaceae, Bacteroidetes, Deinococcus-Thermus, and Firmicutes but also by Acidobacteria, Chlamydiae, Gemmatimonadetes, and Proteobacteria. Thus, BSH and derivatives appear to be the most broadly distributed LMW thiols in biology. IMPORTANCE Low-molecular-weight thiols are key metabolites that participate in many basic cellular processes: central metabolism, detoxification, and oxidative stress resistance. Here we describe a new thiol, N-methyl-bacillithiol, found in an anaerobic phototrophic bacterium and identify a gene that is responsible for its synthesis from bacillithiol, the main thiol metabolite in many Gram-positive bacteria. We show that the presence or absence of this gene in a sequenced genome accurately predicts thiol content in distantly related bacteria. On the basis of these results, we analyzed genome data and predict that bacillithiol and its derivatives are the most widely distributed thiol metabolites in biology.